Evaluating Teachers of International Business Education in NUAA Based on Efficacy Using AHP - Thiranun, Monpattra; Xu, Haiyan (Advances in Social Sciences Research Journal, 2015)
Efficacy evaluation has just become famous in the last decade. This paper aims to show one case study, Efficacy Evaluation of International Business Teacher in NUAA, which being evaluated by students. In the step of design criteria for teacher efficacy evaluation in this case, using concept of four factors model by Brouwers and Tomic (2003) and Student Evaluation Teaching (SET) to design criteria, sub-criteria, and indicators. This paper wanted to show teacher efficacy evaluation by evaluating effectiveness of teacher and setting a goal to achieve. All data in this paper are from asking International Business students to fill the survey. After collecting data, it showed that 76 students in International Business major think that their teachers are efficacious enough in the term of teacher’s personality and given workload, but other criteria should still have some improvements. Finally, the result from this paper can help improving the performance of International Business teachers in NUAA but it does not mean that the improvement is necessary.